Analisis Kualitatif Kandungan Sulfat dalam Aliran Air dan Air Danau di Kawasan Jakabaring Sport City Palembang - Erviana, Desti; Budaya, Annisa Widya; Hariani, Silvi; Winda, Arriya; Sari, Luffiya Yulia (ALKIMIA, 2018)
Analytical chemistry is one branch of chemistry in which there is a way to determine certain ion levels using selective and specific reagents. One type of ion that can be known is the sulfate ion. Sulfate ions are one of the main anions that appear in water naturally. Sulfate is one of the important ions in water availability because of its important effect on humans when it is available in large quantities. The maximum limit of sulfate in water is around 250 mg / L for human-consumed water. This study uses qualitative analysis to determine whether water in the Jakabaring Sport City Palembang region contains sulfate ions or not. Samples taken directly from five different points were reacted with HCl and BaCl2. The results obtained are the five positive water samples containing sulfate ions which are characterized by the formation of white deposits.